Nilai – Nilai Edukatif Dasa Dharma Pramuka Dalam Perspektif Ilmu Pendidikan Islam - Sulaiman, Husnan; Maulana, Ridwan (STAI Al-Musaddadiyah Garut, 2023)
Islamic education, in terms of quality, still needs to improve to align with the times and emphasize character formation in accordance with the values embedded in religious culture, particularly in shaping the character of students. The research problem addressed in this study is: What are the Educational Values of the Scout's Dasa Dharma within the Context of Islamic Education? Based on this formulation, the objective of this research is to understand the Educational Values of the Scout's Dasa Dharma within the Context of Islamic Education. The research method employed is qualitative and is based on library research, involving the examination of written sources relevant to the research topic. The findings of the study conclude that the educational values of the Scout's Dasa Dharma can significantly contribute to the development of character education aimed at shaping students' thought patterns, attitudes, and behaviors, so that they become individuals with noble character, high moral standards, and a sense of responsibility in their lives. These values can cultivate character education in students, guiding them to refrain from actions that could be harmful to themselves and their surroundings. Consequently, the Islamic character values formed are always relevant to the challenges of the times, as Islamic values are universal and can be embraced by all of humanity. Keywords: Educational Values, Scout's Dasa Dharma, Islamic Education